Control of testosterone secretion, musth and aggressive behaviour in African elephant (Loxodonta Africana) bulls using a GnRH vaccine - Bertschinger, H.J. (Hendrik Jan) (University of Pretoria., 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2005.